Evaluasi Kesuksesan Implementasi Sistem Informasi Produksi Udang dengan DeLone and McLean Model - Orza Haidar Hilmy; Admaja Dwi Herlambang; Mochammad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Shrimp Production Information System is made to be able to simplify and accelerate the performance of the employees in managing company data, especially on the Departement of Shrimp Production, it is necessary to evaluate the successful implementation of shrimp production information system. The evaluation was done by using DeLone & McLean Model with six variables. On variable System Quality, Information Quality, Service Quality, Use, User Satisfaction, and Net Benefit. In this study using 2 methods of data retrieval that is interview and observation. The evaluation result two data, that is qualitative descriptive data and reinforced with quantitative data. From the results of evaluation conducted stated that the success of the information system on the variable system quality entered in the high criteria with the obtained is 76%. In the variable information quality entered in the high criteria with the obtained is 72%. In the variable service quality entered in the high criteria with the obtained is 79%. In use variable enter in the very high criteria with the value obtained is 94%. In user satisfaction variable enter in very high criteria with the value obtained is 82%. And in the variable net benefit included in the high enough criteria with the value obtained is 60%. The recommendation given in this research is from the six variables used need to be improved again in order to improve the operational feasibility so that the category can be stable and reach the category Very Played well so that the user feel easy and speed up its performance given by Shrimp Priduction Information System.